Current account and REER misalignments in Central Eastern EU countries: an update using the macroeconomic balance approach - Mariarosaria Comunale (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
Using the IMF CGER methodology, we make an assessment of the current account and price competitiveness of the Central Eastern European Countries (CEEC) that joined the EU between 2004 and 2014. We present results for the "Macroeconomic Balance (MB)" approach, which provides a measure of current account equilibrium based on its determinants together with mis-alignments in real effective exchange rates. We believe that a more refined analysis of the mis-alignments may useful for the Macroeconomic Imbalance Procedure (MIP). This is especially the case for these countries, which have gone through a transition phase and boom/bust periods since their independence. Because such a history may have influenced a country's performance, any evaluation must take account of each country's particular characteristics. We use a panel setup of 11 EU new member states (incl. Croatia) for the period 1994-2012 in static and dynamic frameworks, also controlling for the presence of cross-sectional dependence and checking specifically for the role of exchange rate regimes, capital flows and global factors. We find that the estimated coefficients of the determinants meet with expectations. Moreover, the foreign capital flows, the oil balance, and relative output growth seem to play a crucial role in explaining the current account balance. Some global factors such as shocks in oil prices or supply might have played a role in worsening the current account balances of the CEECs. Having a pegged exchange rate regime (or being part of the euro zone) affects the current account positively. The real effective exchange rates behave in accord with the current account gaps, which clearly display cyclical behaviour. The CAs and REERs come close to equilibria in 2012 in most of the countries and the rebalancing is completed for some countries that were less misaligned in the past, such as Poland and Czech Republic, but also for Lithuania. When Foreign Direct Investment (FDI) is introduced as a determinant for these countries, the misalignments are larger in the boom periods (positive misalignments) whereas the negative misalignments are smaller in magnitude.
URN:NBN:fi:bof-201510131420
Keywords: F31; F32; C23; 330